2020
DOI: 10.21037/atm-20-3371
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of polyphyllin I on myocardial ischemia/ reperfusion injury in rats

Abstract: Background: Myocardial ischemia/reperfusion (I/R) injury has become a global public health concern.An increasing amount of evidence has shown that polyphyllin I (PPI) has anti-apoptotic and antioxidant functions. This study was performed to evaluate the cardioprotective effects of PPI in a rat model of myocardial I/R injury and the underlying mechanism. Methods:We exposed induced a rat model of I/R injury by exposing rat hearts to left anterior descending coronary artery ligation for 30 min, followed by 24 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…It is thought that ROS upregulate IL-1 β through the NLRP3 inflammasome activation and caspase-1 expression [ 121 ]. IL-6 works as a downstream target of IL-1 β [ 159 ]. It was demonstrated that thioredoxin-interacting protein-mediated NLRP3 inflammasome activation in cardiac microvascular endothelial cells was a novel mechanism of MI/RI [ 160 ].…”
Section: Pathways Through Which Oxidative Stress Causes Myocardial Reperfusion Injurymentioning
confidence: 99%
“…It is thought that ROS upregulate IL-1 β through the NLRP3 inflammasome activation and caspase-1 expression [ 121 ]. IL-6 works as a downstream target of IL-1 β [ 159 ]. It was demonstrated that thioredoxin-interacting protein-mediated NLRP3 inflammasome activation in cardiac microvascular endothelial cells was a novel mechanism of MI/RI [ 160 ].…”
Section: Pathways Through Which Oxidative Stress Causes Myocardial Reperfusion Injurymentioning
confidence: 99%
“…NF‐κB was a recognized transcription factor in modulation of inflammation, oxidative stress and cell apoptosis in the context of MIRI 17‐19 . The expression level of phospho‐NF‐κB p65 was significantly upregulated after H/R compared with the control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Middle or high concentrations of ROS could induce inflammatory response and even apoptosis in cardiomyocytes through oxidative stress. 17,22 SOD is the main enzyme that eliminates ROS in cells. It can restore the dynamic balance of oxidation and anti-oxidation, and prevent ROS from causing damage to cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations